1994
DOI: 10.1099/00207713-44-4-798
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral Divergence of Rickettsia bellii from the Spotted Fever and Typhus Groups of Rickettsia and Antiquity of the Genus Rickettsia

Abstract: The eubacterial genus Rickettsia belongs to the cu subgroup of the phylum Proteobacteriu. This genus is usually divided into three biotypes on the basis of vector host and antigenic cross-reactivity characteristics. However, the species Rickettsia bellii does not fit into this classification scheme; this organism has characteristics common to both the spotted fever group and the typhus group biotypes and also exhibits some unique features. Sequences of the 16s rRNA and 23s rRNA genes from Rickettsia rickettsii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 30 publications
3
67
0
7
Order By: Relevance
“…Interestingly, two species in the family Rickettsiaceae, Rickettsia bellii and Orientia tsutsugamushi, also lack a recognizable fmt gene in this position (Andersson et al, 1999). This is consistent with O. tsutsugamushi representing a separate genus (Tamura et al, 1995) and with the suggestion, based on analysis of 16S and 23S rRNA genes (Stothard et al, 1994 ;Stothard & Fuerst, 1995) and the citrate synthase gene (Roux et al, 1997), that R. bellii diverged relatively early in the speciation of the genus Rickettsia.…”
Section: F R Rurangirwa and Otherssupporting
confidence: 75%
“…Interestingly, two species in the family Rickettsiaceae, Rickettsia bellii and Orientia tsutsugamushi, also lack a recognizable fmt gene in this position (Andersson et al, 1999). This is consistent with O. tsutsugamushi representing a separate genus (Tamura et al, 1995) and with the suggestion, based on analysis of 16S and 23S rRNA genes (Stothard et al, 1994 ;Stothard & Fuerst, 1995) and the citrate synthase gene (Roux et al, 1997), that R. bellii diverged relatively early in the speciation of the genus Rickettsia.…”
Section: F R Rurangirwa and Otherssupporting
confidence: 75%
“…Interestingly, the other species that did not yield amplification results were those previously described as being more distant phylogenetically (Sekeyova et al, 2001;Roux et al, 1997;Fournier et al, 1998;Vitorino et al, 2003). Moreover, it has been suggested that R. canadensis and R. bellii, as well as an unidentified bacterium from Adalia bipunctata, were the first representatives of the genus Rickettsia to diverge, and hence they have major genetic differences (Stothard et al, 1994). In view of this fact, the unsuccessful PCR amplification of the Rc-65 locus in these rickettsiae species could mean that they may have different nucleotide sequences in the primer regions.…”
Section: Discussionmentioning
confidence: 98%
“…Second, another experiment was performed using a random sample consisting of 5 phyla, 7 classes and 13 genera and the phylogeny shown in Figure 6 confirms topological accuracy. The only exception seen is due to Rickettsia-bellii which is found to have diverged much earlier from the related organisms [30] and hence its isolation from the rest in the figure. Third, another experiment with a sample consisting of three eukaryotic RNA sequences from brown dog tick, mouse and sand fly as well as 15 organisms of microbial origin was performed.…”
Section: Fig 3 Distance Matrix Using Emm Signature Derived Metricmentioning
confidence: 98%
“…The Rickettsi on the other hand isolates one organism from the other two. Stothard et al proved [30] that the isolated organism Rickettsi1 or Rickettsia-bellii-RML369-C has diverged out of the other genera of Rickettsi much earlier. The distance matrix for this group alone (Figure 7) clearly shows the distinction in the Rickettsi sample.…”
Section: Fig 3 Distance Matrix Using Emm Signature Derived Metricmentioning
confidence: 99%
See 1 more Smart Citation